(untitled) (Global Journal of Management and Business Research, 2019)
This study aims to analyze the determinant of employee performance. Based on theories indicate several variables the company needs to pay attention to, there are job satisfaction, work environment, employee individual commitment and work motivation. The research object is the Small and Medium Enterprises of Cooperative Service (Diskop UKM) in Aceh. The sampling technique used is a census, takes population as a sample, that is as much as 130 people as the respondents. This study also uses Structural Equation Modeling (SEM) to test the causality model. The result shows that job satisfaction effects work motivation significantly, work environment effects work motivation significantly, individual commitment effects work motivation significantly, job satisfaction effects employee performance significantly, work environment effects employee performance significantly, individual commitment effects employee performance significantly, and work motivation effects employee performance significantly in which the Critical Ratio value is greater than 2.00 and the probability level is above 0.05. It means that all hypotheses are verified. The originality lies in the integration model of causality theories from the previous ones, and uses SEM as a test technique. The limitation is in the number of variables and the object. This has the implication of enriching knowledge in the social sciences, and as a basis for further new research models. It also implies practical people who implement related variables.